Raising the standards of patient‐centered outcomes research in myelodysplastic syndromes: Clinical utility and validation of the subscales of the QUALMS from the MDS‐RIGHT project. (19th December 2022) - Efficace, Fabio; Koinig, Karin; Cottone, Francesco; Bowen, David; Mittelman, Moshe; Sommer, Kathrin; Langemeijer, Saskia; Culligan, Dominic; Filanovsky, Kalman; Storck, Michael; Smith, Alexandra; van Marrewijk, Corine; et al.
Abstract: Background: Clinical decision‐making for patients with myelodysplastic syndromes (MDS) is challenging, and both disease and treatment effects heavily impact health‐related quality of life (HRQoL) of these patients. Therefore, disease‐specific HRQoL measures can be critical to harness the patient voice in MDS research. Methods: We report a prospective international validation study of the Quality of Life in Myelodysplasia Scale (QUALMS) with a main focus on providing information on the psychometric characteristics of its three subscales: physical burden (QUALMS‐P), emotional burden (QUALMS‐E), and benefit finding (QUALMS‐BF). The analysis is based on patients enrolled from three European countries and Israel, participating to the MDS‐RIGHT Project. The scale structure and psychometric properties of the QUALMS were assessed. Results: Overall, 270 patients with a median age of 74 years were analyzed and the majority of them (60.3%) had a low MDS‐Comorbidity Index score. Results of the confirmatory factor analysis supported the underlying scale structure of the QUALMS, which, in addition to a total score, includes three subscales: QUALMS‐P, QUALMS‐E, and the QUALMS‐BF. The QUALMS‐P exhibited the highest Cronbach's alpha coefficients. Discriminant validity analysis indicated good results with the QUALMS‐P and QUALMS‐E distinguishing between patients with different performance status, comorbidity, anemia, and transfusion dependency status. No floor and ceiling effects were observed. Responsiveness to change analysis supported the validity of the measure. Patients with a hemoglobin (Hb) level of <11 g/dL at study entry, who subsequently showed an improvement in their Hb levels, also reported a mean score change of 9 and 8 points (scales ranging between 0 and 100) in the expected direction of the QUALMS‐E and QUALMS‐P, respectively. Conclusions: Our study provides additional validation data on the QUALMS from the international MDS‐RIGHT Project. The use of this disease‐specific HRQoL measure may contribute to raise quality standards of patient‐centered outcomes research in MDS. Abstract : The QUALMS is a Patient‐Reported Outcome measure to assess health‐related quality of life in patients with myelodysplastic syndromes. This study, conducted across three European countries and Israel, supports the validity of the QUALMS and provides novel information on the psychometric performance of its three subscales (QUALMS‐P; QUALMS‐E; QUALMS‐BF).